Ag:BiVO4 dendritic hybrid-architecture for high energy density symmetric supercapacitors. Issue 20 (28th April 2016) - Patil, Santosh S.; Dubal, Deepak P.; Tamboli, Mohaseen S.; Ambekar, Jalindar D.; Kolekar, Sanjay S.; Gomez-Romero, Pedro; Kale, Bharat B.; Patil, Deepak R.
Abstract : Hydrothermally synthesized Ag:BiVO4 with a dendritic structure as an excellent electrode material for symmetric supercapacitors. Abstract : We demonstrate the fabrication of Ag:BiVO4 with a dendritic architecture by a template free hydrothermal method. Then, symmetric cells based on Ag:BiVO4 electrodes were assembled which exhibit an extended voltage window of up to 1.6 V with an excellent energy density of 2.63 mW h cm −3 (38.43 W h kg −1 ) and a power density of 558 mW cm −3 (8.1 kW kg −1 ).